Tingkat keparahan halitosis pada manula pemakai gigitiruan - Moh. Dharmautama; Angela Thomas Koyama; Astri Kusumawati (Journal of Dentomaxillofacial Science, 2008)
As the increased of age, the mouth commonly becames dried and could cause difficultyeither in swallowing foods or using denture. The condition could produced a badbreath (halitosis). Study about halitosis in these people becomes interested because ofmany people are using denture nowadays. The aim of this study is determinet the effectof using denture in older with the product of halitosis. The study will evaluated howserious the halitosis condition will happened in the correlation between duration ofusing any kind denture and the product of halitosis.This study perform in MakassarCity, consist of fifty people over sixty years old who still using denture with notsystemic factors in a non random sampling.Conclusion, there is 46 % with medium category byusing rub smell and blowsmelldetections, use using dentures could produced halitosis, compare with the other kindsof denture, partial denture is the most common couse in produced halitosis, and wasinfluenced by the duration of denture.